Performance Comparison of Condensing and Backpressure Steam Turbines: An Industrial Case Study in Cogeneration - Fauzun Atabiq; Robi Kurniawan; Nining Iaanatul Udzmah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
In integrated industrial facilities, selecting the optimal steam turbine configuration requires balancing electrical generation efficiency with overall system energy utilization. This study presents a quantitative comparative performance analysis between a 33 MW condensing steam turbine and a 30 MW backpressure steam turbine operating simultaneously at the cogeneration power plant of PT Bintan Alumina Indonesia. Empirical data were obtained from the plant's Distributed Control System (DCS), consisting of synchronized high-frequency hourly measurements over a 24-hour operational period, including steam flow rate, inlet and exhaust pressure, temperature, and generator load. Thermodynamic analyses based on enthalpy drops across the turbines were performed to calculate isentropic efficiency, specific steam consumption (SSC), and generator efficiency. The condensing turbine achieved higher thermal performance, with an isentropic efficiency of 64.22% and a low SSC of 4.76 t·h⁻¹·MW⁻¹, indicating superior energy conversion efficiency. Conversely, the backpressure turbine exhibited slightly lower isentropic efficiency of 61.70% but demonstrated higher generator conversion efficiency of 95.49% and greater load stability, aligning with process steam requirements. These results empirically confirm a clear operational trade-off: the condensing turbine is optimal for maximizing electrical output, whereas the backpressure turbine enhances overall plant energy recovery and reliability in combined heat and power (CHP) operation. This study provides a robust data-driven benchmark for assessing turbine performance in industrial cogeneration systems and offers practical insights for improving energy efficiency, reducing steam consumption, and supporting sustainable operation in energy-intensive manufacturing industries.